University Autonomy and Academic Freedom: A Historical Perspective - Guruz, Kemal (International Higher Education, 2011)
A brief summary of the historical development of the concepts of academic freedom and university autonomy is presented. Particular emphasis is placed on the changing interpretation of university autonomy that has paralleled the changing role of the state from regulatory to evaluative.